Spectrophtometric Determination of Mesalamine in Pure and Pharmaceutical Formulations - Arbad, B.R.; Jadhav, S.M. (Asian Journal of Chemistry, 2010)
Two simple and sensitive visible spectrophotometric methods for the assay of mesalamine (MA) have been developed. In Method-A, mesalamine forms a violet coloured complex in alkaline medium with 1,2-naphthaquinon-4-sulphonic acid sodium salt reagent. Method-B is based on the oxidation of mesalamine with iron (III), and subsequent chelation of iron(II) with 1,10-phenanthroline (Phen) to form a red coloured complex (λmax 515 nm); the colour so produced is perfectly stable for 24 h. Method A and B obey the Lambert-Beer's law in concentration ranges employed for this method. The results of analysis of both the methods have been validated statistically and by recovery study. The proposed methods are selective, simple and economical for the determination of mesalamine.